Augmented reality using features accelerated segment test for property catalogue - Rudy Setyadi; Indra Ranggadara (Universitas Ahmad Dahlan, 2020)
Promotional media used in the marketing of housing using catalogs that display 2D images of houses from one side of the house make potential customers unable to imagine the design of all parts of the house. Augmented Reality can be used as an interactive marketing media so that it can be used to display homes in 3D so that they appear more real from all sides so that prospective customers can consider the type of house to be chosen. Development of this application using the Multimedia Development Life Cycle. Application development uses the FAST algorithm as detection of home catalog markers to define how well images can be detected and tracked. The FAST algorithm will calculate every pixel on the target image in determining the corner when scanning the home catalog then it will produce a 3D object home to see the real shape design of the house.